(untitled) (Third Sector Social Economic Review, 2022)
In this study, the concept of self, which is defined as the way of perceiving oneself, and its place in marketing discipline researches are examined. A compilation has been made on the literature describing the theory and development of the self-concept, theoretical articles that establish its relationship with marketing, and quantitative research articles aimed at understanding consumer behavior. The findings of the study can be used to understand the components of self-concept which affect consumer behavior, such as how the person sees himself, what his thoughts and expressions about his personality are, and to develop marketing decisions according to this understanding. The self can be considered in two dimensions, the real self and the ideal self. The real self is the answer to the question ""who am I"", the ideal self is the answer to ""who do I want to be"". The purpose of people is to bring their real selves closer to their ideal selves. When people take on the role of consumers, they can achieve these goals through what they want to buy and own. When the real motivations underlying the purchasing behavior of consumers are examined, it has been observed that they do not always act rationally and that factors other than functional benefits are also important. Consumers who see owning a product and brand as a means of self-expression can be understood with an extended-self theory that can be defined as ""you become what you own"".